2017
DOI: 10.1111/1462-2920.13924
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of ectoine catabolism in response to multiple metabolic and environmental cues

Abstract: Ectoine and hydroxyectoine are effective microbial osmostress protectants, but can also serve as versatile nutrients for bacteria. We have studied the genetic regulation of ectoine and hydroxyectoine import and catabolism in the marine Roseobacter species Ruegeria pomeroyi and identified three transcriptional regulators involved in these processes: the GabR/MocR-type repressor EnuR, the feast and famine-type regulator AsnC and the two-component system NtrYX. The corresponding genes are widely associated with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(95 citation statements)
references
References 89 publications
5
90
0
Order By: Relevance
“…Both MIB and teleocidin B were important terpenoids and they were synthetized by terpene synthases[ 35 , 38 ]. Ectoine was an effective microbial osmostress protectant, which could also serve as a versatile nutrient[ 39 ]. Furthermore, the similarities of cluster 7, cluster 10, cluster 22, cluster 30, cluster 31, and cluster 34 with their similar and known gene clusters were all more than 60%, which might indicate the biosynthesis ability of hopene, lantipeptide, cyclooctatin (a kind of siderophore), albachelin, and candicidin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both MIB and teleocidin B were important terpenoids and they were synthetized by terpene synthases[ 35 , 38 ]. Ectoine was an effective microbial osmostress protectant, which could also serve as a versatile nutrient[ 39 ]. Furthermore, the similarities of cluster 7, cluster 10, cluster 22, cluster 30, cluster 31, and cluster 34 with their similar and known gene clusters were all more than 60%, which might indicate the biosynthesis ability of hopene, lantipeptide, cyclooctatin (a kind of siderophore), albachelin, and candicidin.…”
Section: Resultsmentioning
confidence: 99%
“…Some gene clusters in these two strains might improve the resistance of peony for the environmental stress. For example, the presence of synthetic gene cluster of ectoine [ 39 ] in both strains might improve the salt stress of peony in saline-alkali land. At present, the research on Streptomyces strains as PGPR has been carried out [ 16 , 17 ], but there were relatively little biocontrol study and genome research about species S. albireticuli and S. alboflavus.…”
Section: Discussionmentioning
confidence: 99%
“…Microscale thermophoresis experiments demonstrated that R. pomeroi EnuR binds two metabolites of ectoine catabolism N‐(α)‐ADABA ( K d = 1.7 μ m ) and DABA ( K d = 457 μ m ), which act as effector molecules, whereas it does not bind N‐(γ)‐ADABA, an intermediate in ectoine biosynthesis. These results demonstrated that EnuR is a key regulator for microorganisms that use ectoines as nutrient because it showed high affinity for N ‐α‐ADABA, an ectoine‐catabolism‐specific metabolite, low affinity for DABA, that is an intermediate in other metabolic and biosynthetic processes, including the biosynthesis of ectoine, and has no affinity for N‐(γ)‐ADABA, which serves as the main substrate for the ectoine synthase .…”
Section: Cofactor and Effector Binding Properties Of Mocr‐tfsmentioning
confidence: 95%
“…EnuR is transcribed from its own promoter and, in fact, its transcriptional level is low and independent from the available substrates, whereas the uehABC‐eutABC ‐ eutDE‐ssd‐atf transcript is strongly up‐regulated in cells grown on a medium containing either ectoine or 5‐hydroxyectoine. The loss of the EnuR regulator does not affect expression from the enuR promoter but results in a constitutive expression from the substrate‐inducible uehA promoter, demonstrating that EnuR acts as a repressor .…”
Section: Characterised Mocr‐tfs and Their Functional Characteristicsmentioning
confidence: 99%
“…Finally, ectoines are not only effective osmostress protectants but they are also valuable nutrients for microorganisms [ 24 ]. The physiology and genetics of the catabolism of these nitrogen-rich compounds ( Fig 2 ) have been intensively studied in the marine bacterium Ruegeria pomeroyi [ 53 ]. A unique ectoine-derived metabolite (N-α-L-acetyl-2,4-diaminobutyric acid), and not ectoine or hydroxyectoine themselves, serves as the inducer for the GabR/MocR-type regulatory protein EnuR that controls the transcription of the ectoine/5-hydroxyectoine import and catabolic gene clusters present in many microorganisms [ 53 ].…”
Section: Halophilic Protists—how Do They Do It?mentioning
confidence: 99%